Institutional Collaboration in the Governance and Development of Mangrove Forest Ecotourism in Langsa City, Aceh - Saputra, Akmal; Masrizal, Masrizal; Marefanda, Nodi; Turrahmi, Hanifah; Maisyura, Maisyura; Hidayat, Amri Wahid (Journal of Social and Policy Issues, 2025)
The development of mangrove forest tourism in Langsa City requires cooperation from various stakeholders. The phenomenon of tourist destinations in the era of globalization continues to grow and advance, giving rise to creative and innovative ideas that make these tourist attractions unique and attractive to visitors. This study investigates the cooperative initiatives in the management and promotion of mangrove forest ecotourism in Langsa City, Aceh. This study seeks to clarify how stakeholder collaboration might promote the growth and improvement of mangrove forest ecotourism. The collaboration among institutions is the principal strength in the progression of ecotourism, where support from all stakeholders is essential for the development process to proceed as expected. This study utilizes a qualitative technique, including data collection methods like observation, in-depth interviews, and documentation. The research findings indicate that collaboration among various stakeholders, including the mangrove forest manager PT. PEKOLA (a regional enterprise), the local government (particularly the Youth, Sports, and Tourism Office), universities, customary institutions (such as village heads and the Aceh Customary Council), and banking, has been successfully established. Each stakeholder is essential in the governance and development of mangrove ecotourism, whether as policymakers, implementers, or advocates for mangrove forest conservation.